PENGARUH JENIS KECERDASAN TERHADAP HASIL BELAJAR TOPIK ALJABAR KELAS VIII MTSN SE-KOTA PADANGSIDIMPUAN - Ahmad Nizar Rangkuti; Sojuangon Rambe (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2016)
This research aims to explore the effect of the seven major kinds of human intelligence identified by Howard Gardner (1983) on students’ ability to solve mathematical problems specifically in Algebra topic. This research involves about 115 participants randomly taken from whole tested population. Data collection was conducted by introducing test and questionnaire. The hypothesis examination resulted that hypothesis was accepted at index: Fcount 2.327 Ftable 2.09 in significance level α=0.05. By using the Scheffe’s formula, order of sequence of ability to solve algebra’s problems based on the intelligence types was: Logical-mathematics Bodily-Kinesthetic Intrapersonal Interpersonal Linguistics Spatial Musical.